Comparative Structural Analysis of Intake Well Models Using Staad.Pro: Evaluating Displacements, Shear Forces, and Bending Moments - Divyanshu Jhadane; Dr. Abhay Kumar Jha (International Journal of Scientific Research in Civil Engineering, 2025)
This study conducts a detailed structural performance evaluation of two intake well models (Model 1 and Model 2) using STAAD.Pro under various loading conditions. Critical response parameters including nodal displacements, shear forces, axial forces, and bending moments are analyzed along different heights and axes to assess structural behavior. Results indicate that Model 2 exhibits superior performance, with significantly reduced displacements at higher elevations (0 mm at 35 m vs. 129.57 mm in Model 1), optimized shear force distribution (zero shear at critical upper sections), and improved bending moment resistance (1355.379 KN-m vs. 1409.069 KN-m in Model 1 at 35 m). The findings highlight Model 2’s enhanced stiffness, better load distribution, and greater resilience against seismic and operational forces. Recommendations include adopting Model 2’s design refinements, further optimizing base-level reinforcement, and conducting dynamic analysis for real-world validation. This research provides valuable insights for improving the structural efficiency and safety of water intake well systems.